Malory towers: winter term: book 9 - Cox, Pamela; Enid, Blyton (London : Hodder children books, 2019)
Enormously popular all over the world, Enid Blyton's school series combines everything that makes school so special - friendships, learning, sports, plays and mischief!
Keywords: English - Teenage fiction book